Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.